Analisis Penambahan Nutrisi Pada Tanaman Hidroponik Berbasis Internet of Things - Priya Surya Harijanto; Masramdhani Saputra; Oky Achmad E; Muhammad Fahmi Hakim (Politeknik Negeri Malang, 2022)
In an increasingly advanced era, electrical energy has become a basic resource for humans, the wider and more equitable distribution has greatly influenced the progress of all sectors of electricity users. However, on the other hand, this hydroponic business requires precision and special attention by the actors to support the maximum success of the hydroponic business. Several previous tools have been able to overcome the problem of irrigation for hydroponic plants. However, there is no tool that can regulate the addition of nutrients based on the internet of things and monitor the hydroponics. So, a tool for adding nutrients to hydroponic plants based on the internet of things was designed that is equipped with supervision on plant nutrition. It is hoped that after the manufacture and analysis of tools on hydroponic plants can overcome the problems that are often experienced by hydroponic entrepreneurs.The research was conducted from May to July 2022 in Margoutomo Dalam, Dau, Malang. This nutrient addition tool is designed using an Arduino Uno microcontroller where as a regulator and NodeMCU is added as an online access on the user's cellphone. After the tool has been designed, a regression analysis is carried out to determine the effect of nutrient levels on the fertility of hydroponic plants. The results of this study showed that the nutritional value of a good plant was 350 ppm, with the response rate of this nutrition enhancer at 1.62% per second at a distance of 338 km for testing the user.